Sistem Pendukung Keputusan Penerima Bantuan pada Program Keluarga Harapan Menggunakan Metode Topsis: (Studi Kasus: Pkh Desa Pogo Tena) (Mars: Jurnal Teknik Mesin, Industri, Elektro Dan Ilmu Komputer, 2026)
This research aims to design and develop a decision support system to determine the recipients of assistance in the Family Hope Program (PKH) in Pogo Tena Village. This system uses the (Technique for Order Preference by Similarity to Ideal Solution) method which aims to assist decision-makers in selecting families who meet the criteria to receive social assistance based on several predetermined factors, such as income level, number of family dependents, health conditions, and education. The method used in this study is a qualitative and quantitative method with a case study approach on PKH Pogo Tena Village. Data was obtained through interviews with related parties, field observations, and data collection from existing documents. In this system, the assessment is carried out by comparing alternative performance values based on pre-established criteria, and then using the TOPSIS method to determine the families who are eligible for assistance. The results of this study show that the designed decision support system can provide more objective and transparent recommendations for aid recipients. Using the TOPSIS method, the system can prioritize beneficiaries based on their proximity to the ideal solution, which helps minimize subjective errors in the beneficiary selection process. This research is expected to contribute to increasing the effectiveness and efficiency in the implementation of the Family Hope Program in Pogo Tena Village, as well as as a reference for other agencies that want to apply similar methods in social assistance programs.